A Case of Multifocal Eosinophilic Granuloma Involving Spine and Pelvis in a Young Adult: A Radiopathological Correlation - Rai, Santosh; Sridevi, H B; Pai, Radha R; Sanyal, Pulastya (Indian Journal of Medical and Paediatric Oncology, 2017)
We present a case of multiple osteolytic lesions in a 28-year-old adult who presented with headache, back pain, and hip pain of 6 months. There was no history of localized swelling or rise of temperature, no history of weight loss or evening rise of temperature. On examination, there were no focal neurological deficits. Routine laboratory investigations, including total leukocyte counts, differential leukocyte counts, hemoglobin, and platelet counts, were within normal limits. There was a borderline elevation of erythrocyte sedimentation rate. Non enhancedcomputer tomography (NECT) demonstrated no abnormality in the brain or skull bones. However, incidentally, a lytic lesion involving the third cervical (C3) vertebral body and the neural arch was detected which also demonstrated a soft tissuecomponent adjacent to the lytic lesion. These findings warranted further work up; and magnetic resonance imaging of whole spine and pelvis was performed that revealed multiple bony lesions involving the cervical vertebrae, head and neck, bilateral femur, sacrum, and iliac bones. Computed tomography-guided biopsy was performed from the C3 vertebral lytic lesion which showed features of eosinophilic granuloma on histopathological evaluation.
Keywords: Eosinophilic granuloma; multiple lytic lesions; radiological